The pass-through of temporary VAT rate cuts: Evidence from German retail prices - Clemens Fuest; Florian Neumeier; Daniel Stöhlker (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
On 1 July 2020, value added tax (VAT) rates were reduced in Germany to fight the economic consequences of the Corona pandemic. The VAT rate reduction is temporary as rates will return to their previous level on 1 January 2021. We study the effects of the temporary VAT rate cut on German supermarket retail prices using an extensive webscrapped data set covering the daily prices of roughly 190,000 products. To identify the causal price effects, we compare the development of prices in Germany to those in Austria. Our findings indicate a nearly full pass-through of the VAT rate reduction on prices. On average, prices in German supermarket retail decreased by 2% after the implementation of the VAT rate reduction. We also provide evidence that prices in more competitive product markets decreased to a larger extent.
Keywords: E31; H22; H25; 330; value added tax; tax incidence; price effects; competition